Analysis of the improvement effect of Astragalus extract on oxidative stress injury in viral myocarditis through STAT3/IL-6: Astragalus extract inhibits myocardial inflammation - Chang, Zhiyue; Zhang, Yanhui; Wang, Lu; Wang, Huizhen; Tian, Ling; Qiao, Juan (Cellular and Molecular Biology, 2023)
The objective of this study was to investigate the improvement effect of Astragalus (AS) extract on oxidative stress (OS) and inflammatory response of myocarditis (MYO) cells through the STAT3/IL-6 axis. For this purpose, The MYO model cells prepared by intervening cardiomyocyte HL-1 with Coxsackievirus B3 (CVB3) were divided into four groups: model group, as well as high- (H-), medium- (M-) and low-dose (L-) AS groups treated by 80, 40, and 20 μg/mL AS, respectively. Conventionally cultured cells were set as the normal group. Cell multiplication and apoptosis, as well as levels of Myocardial injury markers (cTnT, BNP and CK), inflammatory cytokines (ICs; TNF-α, IL-1β and IL-6) and OS indices (SOD, GSH-Px and MDA), were measured. STAT3/IL-6 pathway expression was also observed. Results showed that the model group presented decreased cell multiplication than the normal group, but with increased myocardial injury, apoptosis rate, Caspase3 protein, ICs and OS reaction (P < 0.05); In the three AS-intervened groups, enhanced cell multiplication, while reduced myocardial injury, apoptosis rate, ICs and OS response were observed, especially in H-AS group (P < 0.05). Besides, STAT3 and IL-6 concentrations, statistically increased in the model group, were reduced by AS intervention (P < 0.05). Colivelin, a specific activator of STAT3, further aggravated the apoptosis, inflammatory reaction and OS response of MYO cells (P < 0.05), but its impacts on MYO cells could be reversed by AS. In conclusion, AS can ameliorate MYO, and its mechanism is related to the inhibition of cellular inflammatory response and OS response through the STAT3/IL-6 axis.